School Dictionary Entries with a Pedagogical and Linguistic Approach - BENZER, AHMET (My University, 2024)
Dictionaries are reference books and online databases that contain information about the meaning of a word and its most correct use in speech. The headwords and definitions of dictionaries vary depending on the target users of the dictionary, the purpose of editing, and the type of dictionary. School dictionaries are works that should be prepared by taking into account pedagogical concerns as well as lexicography and linguistics. A dictionary entry contains a headword and its explanations (definition, grammatical function labels, pronunciation, illustrations, etc.), and this unit is called microstructure in lexicography. This study aims to create a list of what kind of structures (e.g. part of speech labels, example sentences, etc.) an entry in the school dictionary may contain, taking into account linguistic and pedagogical concerns, and then to develop an entry scheme for Turkish school dictionaries based on this list. For this purpose, in our qualitative research, the descriptive method, which is frequently preferred in lexicography studies that determine the current situation in dictionaries, was preferred. The linguistic and pedagogical features included in a school dictionary entry were obtained through content analysis from 3 different languages (Turkish, English and French) and 3 different school dictionaries (Türk Dil Kurumu [TDK], Cambridge and Le Robert) selected as research object. As a result of the study, it was observed that the school dictionary entry contained 6 different structures in the headword part and 21 different structures in the definition part. There are 1 pedagogical and 5 linguistic structures in the headword. There are 10 pedagogical and 11 linguistic structures in the definition. According to the data obtained, the pedagogical structures in school dictionaries were mostly used to make the use of the headword more concrete. For example, while indicating the part of speech functions of a word is a linguistic feature, it is pedagogical to give an example usage that clearly indicates the grammatical function of the word. As a result of this study, it was suggested that Turkish school dictionaries include structures such as illustrations and example sentences that will concretize the headword. Unlike English and French, Turkish has a flexible system in which words can have various grammatical functions, that is, the grammatical function of a word with the same morphological appearance (a word that does not have a special suffix for adverbs or adjectives) changes depending on the context, the importance of including an example sentence indicating each grammatical function of the word has been emphasized. As a result of the research, an ideal school dictionary entry scheme was proposed.

Sözlükler, bir kelimenin anlamı ve söylevdeki en doğru kullanımı hakkında bilgi içeren kaynak eserler ve çevrim içi veri tabanlarıdır. Sözlüklerin madde başları ve tanımları sözlüğün hedef kullanıcılarına, düzenlenme amacına ve sözlüğün türüne göre değişmektedir. Okul sözlükleri sözlük bilimi ve dil biliminin yanı sıra pedagojik kaygıları da dikkate alarak hazırlanması gereken eserlerdir. Bir sözlük maddesi, bir madde başı kelime ve onun açıklamalarını (tanım, dil bilgisel işlev etiketi, telaffuz, illüstrasyonlar vb.) içerir ve bu birime sözlük biliminde parçacıl yapı adı verilir. Bu çalışmada okul sözlüğündeki bir maddenin dil bilimsel ve pedagojik kaygılar dikkate alınarak ne tür yapılar (örneğin kelime türü etiketleri, örnek cümleler vb.) içerebileceğinin bir listesinin oluşturulması, ardından bu listeye dayanarak Türkçe okul sözlükleri için bir sözlük maddesi şeması geliştirilmesi amaçlanmaktadır. Bu amaç doğrultusunda nitel araştırmamızda, sözlük bilimi araştırmalarında sözlüklerde var olan durumu tespit eden çalışmalarda sıklıkla tercih edilen betimleyici yöntem tercih edilmiştir. Bir okul sözlüğü maddesinde yer alan dil bilimsel ve pedagojik özellikler, araştırma nesnesi olarak seçilen 3 farklı dilden (Türkçe, İngilizce ve Fransızca) ve 3 farklı okul sözlüğünden içerik analizi yoluyla (Türk Dil Kurumu [TDK], Cambridge ve Le Robert) elde edilmiştir. Çalışma sonucunda, okul sözlüğü maddelerinin madde başı bölümünde 6, tanım bölümünde 21 farklı yapı içerdiği gözlemlenmiştir. Madde başında 1 adet pedagojik ve 5 adet dil bilimsel yapı bulunmaktadır. Tanımda ise 10 adet pedagojik ve 11 adet dil bilimsel yapı bulunmaktadır. Elde edilen verilere göre okul sözlüklerinde yer alan pedagojik yapılar çoğunlukla madde başı kelimenin kullanımını daha somut hâle getirmek amacıyla kullanılmıştır. Örneğin, kelimenin türünü belirtmek dil bilimsel bir özellik iken kelimenin dil bilgisi bakımından işlevini açıkça belirten bir örnek kullanım vermek pedagojiktir. Bu çalışma sonucunda Türkçe okul sözlüklerinde madde başı kelimeyi somutlaştıracak resim ve örnek cümle gibi yapılara yer verilmesi önerilmiştir. İngilizce ve Fransızcadan farklı olarak Türkçe, kelimelerin çeşitli dil bilgisel işlevlere sahip olabilmesi bakımından esnek sisteme sahip olduğundan yani morfolojik açıdan aynı görünümdeki bir kelimenin (zarflara veya sıfatlara özel bir son ek almamış kelime) dil bilgisel işlevi bağlama göre değiştiğinden kelimenin sahip olduğu her dil bilgisel işlevi belirten örnek bir cümleye yer verilmesi gerektiğinin önemi vurgulanmıştır. Araştırma sonucunda ideal bir okul sözlüğü maddesi şeması önerilmiştir.
Pedagojik ve Dil Bilimsel Yaklaşımla Okul Sözlüğü Maddeleri
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Social Sciences and Humanities; Sociology; Education; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Definiton; Lexicography; Linguistics; Microstructure; School dictionary; Turkish education; Tanım; Sözlük bilimi; Parçacıl yapı; Okul sözlüğü; Türkçe eğitimi; Dil bilimi